Impact of Theater Drama in Developing Positive Practices and Tolerance among a Sample of Special Needs Students - Ayada Ayoub Alkubaisy, Amer; Ramadan Zahran, Ayman (International Journal of Psychosocial Rehabilitation, 2020)
Summary: The current study aimed at identifying the role of theater drama in developing positive practices and tolerance among a sample of 25 students with special needs at the Sheikh Rashid bin Saeed Islamic Institute in Dubai in the preparatory and secondary stages. The study depended on the semi-experimental approach that is based on one group; the study sample received a number of theaters that discussed a number of positive practices and tolerance. The researchers prepared a questionnaire for each of the positive practices and tolerance, which were applied before and after the study sample. Findings indicated that there are statistically significant differences at the level (0.05) between the average levels of pre- and post-application in favor of post-application in both positive practices and tolerance.